THE EFFORTS TO IMPROVE PRODUCTS FOR DEVELOPMENT OF MICRO SMALL MEDIUM ENTERPRISES (MSMEs) BASED ON DIGITAL CREATIVE ECONOMY IN THE SOUTH TANGERANG REGION - Sri Yulianti; Maya Sova; Titus Indrajaya; Mei Supriani; Rushadiyati Rushadiyati; Christina Christina; Septi Nur Aliva (International Journal of Engagement and Empowerment, 2022)
Social media platforms are noteworthy today, characterized by significant advancements in information and communication technologies. Therefore, SME marketing must be able to take advantage of Smart Phone-Online- Based marketing through online digital media. Online Sales Applications, as well as promotion and marketing of SME products by utilizing Social Networks, so that they can become media that can represent products needed by consumers. One of the obstacles encountered by SMEs in the South Tangerang City area. This Community Service (PKM) provides mentoring training for Micro, Small, and Medium Enterprises (MSMEs) online shops based on a creative digital economy in South Tangerang City. This community aims to increase MSME actors' income by training to create online stores, editing product photos, and expanding networks (networks), documentation, and publications. From the activity results, digitalization efforts for creative economy business actors and MSMEs can be achieved by digitalizing the economy and digitizing legal entities by establishing and registering business entities, registering Intellectual Property Rights online, and registering for online NIB (Business Permit Numbers).In addition, online Single Submission (OSS) is risk-based in business licensing. Meanwhile, economic digitization can be achieved by participating in online and offline training, doing online marketing on social media; Instagram, Facebook, Linkedin, TikTok, and the marketplace, and obtaining tips for successful business on the government's official website and digital social media